Romania - Restructuring for EU Integration--The Policy Agenda : Country Economic Memorandum, Volume 2. Main Report and Annexes - World Bank (Washington, DC, 2013)
This Country Economic Memorandum (CEM) looks at the broad reform program, including institutional, governance, and economic restructuring reforms Romania is pursuing, which are anchored in its process for accession to the European Union (EU). The challenge is to expand integration with the EU more broadly throughout the economy, by relying on market driven mechanisms in a predictable rules-based policy environment, with the state sharply focused on the provision of essential public goods. Implementing the institutional reform agenda is the first priority in the accession-led reform, having the country the largest increase in its share of EU external imports among the Central Eastern European Countries (CEECs), with trade diversification providing a robust foundation for trade expansion. But, to deepen trade integration, Romania would need to broaden its trade performance throughout the economy. On restructuring the enterprise sector, the CEM indicates enterprise reform needs to be accelerated, and budget constraint discipline needs to be extended to the transaction interface between the state and enterprises. As for implementing agricultural transformation, the potential competitiveness of agriculture, associated with Romania's moderate climate, and the availability of land, remains largely untapped. Therefore, agricultural policies and transformation need to be driven by competitiveness. Moreover, increased labor market flexibility is needed to improve sectoral employment imbalances, and competitiveness, and hence reduce the risks to the sustainability of growth, as competing in the EU, and global markets becomes increasingly more difficult. Notwithstanding recent progress, there are risks and vulnerabilities to the macroeconomic stabilization, and reform achievements. The energy sector in Romania has been a main source of persistently large quasi-fiscal deficits, more so than in many other transition economies, with high hidden subsidies, and losses in the energy sector. Completing the energy sector reform is essential, but the challenge is to implement budget constraints between the state and energy enterprises, so as to complete the restructuring of the energy sector. Further recommendations include elimination of quasi-fiscal financing, replaced by efficient financial intermediation, and strengthening the regulatory and supervisory infrastructure; deepening the reforms of the social security system; and, containing the costs of upgrading environmental standards.